NARRATIVE REVIEW: THE IMPACT OF BLUE LIGHT EXPOSURE ON MENTAL HEALTH AND CIRCADIAN RHYTHM - Michał Gniedziejko; Jakub Roszak; Paulina Bernecka; Oliwia Sójkowska-Sławińska; Anna Leśniewska; Patryk Macuk; Natalia Strumnik; Klaudia Malec; Julia Konat (International Journal of Innovative Technologies in Social Science, 2025)
Increasing exposure to blue light is a major problem in the modern lifestyle of individuals. The increasing use of digital devices and LED lighting is recognised as a major environmental factor affecting human health. While it has a positive effect on alertness during the day, excessive or late-night exposure disrupts the circadian rhythm by affecting the intrinsically photosensitive retinal ganglion cells (ipRGCs), which regulate melatonin secretion and the sleep-wake cycle. The main negative consequences of evening blue light exposure include: disrupted sleep architecture, particularly by reducing slow-wave and REM sleep, which are essential for recovery processes, impaired cognitive performance, increased daytime sleepiness and a higher risk of mood disorders, including depression and anxiety. Interventions and prevention strategies aimed at reducing evening blue light (through filters, night mode settings or glasses) and morning exposure to bright light have been shown to be beneficial for sleep quality, circadian phase regulation and mood stabilisation. Despite progress in this area, there are still significant research gaps, particularly in relation to individual differences in light sensitivity, long-term effects and the optimal timing and intensity of interventions. This review summarises the latest results of 33 studies and provides a structured overview of the current evidence on the short- and long-term effects of blue light on circadian rhythms, sleep and mental health. It highlights practical measures to minimise harmful exposure suggesting the directions for future research to promote circadian health and general well-being in the context of modern lifestyles.